Description of the operators and isomorphisms of the space of continuous functions commuting with the operator of multiplication - Berezovsky, N. I.; Linchuk, S. S. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We propose the description of the operators and isomorphisms of the space C[a, b] commuting with the operator of multiplication by a continuous strictly piecewise monotone function.